Pemberdayaan Industri Kecil di Pedesaan (Studi Upaya Peningkatan Keberdayaan Pengrajin Kain Tenun Sambas Di Desa Sumber Harapan Kecamatan Sambas Kabupaten Sambas Kalimantan Barat) - Kartika - Ningtias; Irwan - Noor (Wacana Journal of Social and Humanity Studies, 2009)
Sambas traditional woven clothes produced in Sumber Harapan Village, Sambas Regency, are not known in neighboring sub-district and regency areas, but also in Pontianak City and even in Malaysia. Although many mid-scale and large organizations went bankrupt because of the tough economic crisis, this small-scale businesses remain operating without any serious hindrance. This proved that small-scale industries do not assign our government any burdens. Concerning this fact, it is recommended that these industries should be empowered.Underlined by these fact, this study is intend to investigate: (1) Some attempts of sambas woven clothes craftmen to raise their empowerment in order to optimize their business potentials, (2) Sambas Regency Government and private sector roles, and (3) sambas traditional woven clothes empowerment process in Sumber Harapan Village, Sambas Regency.The results identify that the craftmen attempts in optimizing their business potentials contain the following values: (a) economical values, covering income raise, family welfare and family existence and their business; (b) social values, covering aspects of increasing craftmen dignity and social status in which they should operate their own business instead of being workers; (c) cultural values, covering their braveness, struggle, creativity, productivity and will to improve woven cloth design. The small-scale industries have provided economic sources, but they still cannot improve craftmen economic continuously.Sambas Regency Government roles as facilitator agency for the small-scale business has made some efforts by releasing some policies and small-scale industries empowerment. Unfortunately, these efforts has produced optimal outcome. To make the same efforts, private business offers partnership plan through merchandising and production patters.The craftmen empowerment is applied through three phases: initial, guidance, help, and establishment. The craftmen position from their initial existence up to economic crisis of 1997-1998 is emansipatory position. This position has improved into empowerment process at the second year of the economic crisis.Â Keywords: Small-Scale Industry, Empowerment, Rural areas